The expanding phenotype of OFD1‐related disorders: Hemizygous loss‐of‐function variants in three patients with primary ciliary dyskinesia. Issue 9 (1st August 2019) - Hannah, William B.; DeBrosse, Suzanne; Kinghorn, BreAnna; Strausbaugh, Steven; Aitken, Moira L.; Rosenfeld, Margaret; Wolf, Whitney E.; Knowles, Michael R.; Zariwala, Maimoona A.
Abstract: Background: OFD1 has long been recognized as the gene implicated in the classic dysmorphology syndrome, oral‐facial‐digital syndrome type I (OFDSI). Over time, pathogenic variants in OFD1 were found to be associated with X‐linked intellectual disability, Joubert syndrome type 10 (JBTS10), Simpson‐Golabi‐Behmel syndrome type 2 (SGBS2), and retinitis pigmentosa. Recently, OFD1 pathogenic variants have been implicated in primary ciliary dyskinesia (PCD), a disorder of the motile cilia with a phenotype that includes recurrent oto‐sino‐pulmonary infections, situs abnormalities, and decreased fertility. Methods: We describe three male patients with PCD who were found to have hemizygous pathogenic variants in OFD1, further supporting that PCD is part of a clinical spectrum of OFD1 ‐related disorders. In addition, we provide a review of the available clinical literature describing patients with OFD1 variants and highlight the phenotypic variability of OFD1 ‐related disease. Results: Some individuals with hemizygous OFD1 variants have PCD, either apparently isolated or in combination with other features of OFD1 ‐related disorders. Conclusion: As clinicians consider the presence or absence of conditions allelic at OFD1, PCD should be considered part of the spectrum of OFD1 ‐related disorders. Understanding the OFD1 ‐related disease spectrum may allow for more focused genetic testing and more timely management of treatable sequelae. Abstract : Some individuals with hemizygous OFD1 variants have primary ciliary dyskinesia (PCD), either apparently isolated or in combination with other features of OFD1 ‐related disorders. As clinicians consider the presence or absence of conditions allelic at OFD1, PCD should be considered part of the spectrum of OFD1 ‐related disorders. Understanding the OFD1 ‐related disease spectrum may allow for more focused genetic testing and more timely management of treatable sequelae.